Circulating miRNAs as Diagnostic and Prognostic Biomarkers in High-Grade Gliomas - Wu, Jianing; Al-Zahrani, Abdulrahman; Beylerli, Ozal; Sufianov, Rinat; Talybov, Rustam; Meshcheryakova, Svetlana; Sufianova, Galina; Gareev, Ilgiz; Sufianov, Albert (Frontiers in Oncology, 2022)
Objectives: miR-181a/b and miR-410 downregulation and miR-155 upregulation has been shown to play important roles in the oncogenesis and progression of gliomas including high-grade gliomas. However, the potential role of plasma miR-181a/b, miR-410 and miR-155 in the diagnosis and prognosis of high-grade gliomas remains poorly known. Methods: We retrieved published articles from the PubMed, the Cochrane Central Register of Controlled Trials, and Web of Science database and obtained different sets of data on microRNAs (miRNAs) expression profiling in glioma and highlighted the most frequently dysregulated miRNAs and their gene-targets in high-grade gliomas. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was carried out to measure the pre- and postoperative plasma levels of miR-181a/b, miR-410 and miR-155 in 114 Grade 3-4 glioma patients, 77 Grade 1-2 glioma patients and 85 healthy volunteers as control group. The diagnostic and prognostic value of circulating miR-181a/b, miR-410 and miR-155 as biomarker was estimated by the Receiver Operating Characteristic (ROC) curve and the area under the curve (AUC) and Kaplan–Meier analysis. Results: We found a plasma miRNA signature including three downexpressed miRNAs and one overexpressed (miR-181a, miR-181b and miR-410; miR-155) in high-grade glioma patients in comparison with low-grade glioma patients control group. The ROC curve AUC of these four circulating miRNAs were ≥ 0.75 for high-grade glioma patients in before and after surgery. Higher circulating miR-155 and lower miR-181a/b and miR-410 expression is associated with clinical data, clinic pathological variables, worse overall survival (OS) of patients and negative correlated with potential gene-targets expression. Moreover, Kaplan–Meier analysis showed that miR-181a/b, miR-410 and miR-155 were independent predictors of OS in high-grade glioma patients. Conclusions: Our data, for the first time, demonstrated that circulating miR-181a/b, miR-410 and miR-155 could be a useful diagnostic and prognostic non-invasive biomarkers in high-grade gliomas.